2021
DOI: 10.1007/s10238-021-00765-1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of methylprednisolone therapy in patients with a high-risk common type of COVID-19 pneumonia: a retrospective cohort study

Abstract: The optimal timing of glucocorticoid treatment for coronavirus disease 2019 (COVID-19) pneumonia is uncertain. We evaluated the clinical outcomes of methylprednisolone therapy (MPT) for patients with a high-risk common type (HRCT) COVID-19 pneumonia. We conducted a multicenter retrospective cohort study in Northeast China. A comparison was performed between the standard treatment (SDT) group and the SDT + MPT group to determine the efficacy of methylprednisolone in treating HRCT COVID-19 pneumonia. We collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…11 Severe COVID-19 is defined when a patient meets one of the following criteria: (1) respiratory rate ≥30x /minute; (2) blood oxygen saturation ≤ 93% at rest; (3) the partial pressure of arterial oxygen (PaO2) to the fraction of inspired oxygen (FiO2) ≤ 300 mmHg (1 mmHg = 0.133kPa); (4) and pulmonary infiltration > 50% in 48-72 hours. 16 These criteria indicated that there were 5 out of 7 patients were categorized as severe COVID-19 sufferers in this case series.…”
Section: Discussionmentioning
confidence: 91%
“…11 Severe COVID-19 is defined when a patient meets one of the following criteria: (1) respiratory rate ≥30x /minute; (2) blood oxygen saturation ≤ 93% at rest; (3) the partial pressure of arterial oxygen (PaO2) to the fraction of inspired oxygen (FiO2) ≤ 300 mmHg (1 mmHg = 0.133kPa); (4) and pulmonary infiltration > 50% in 48-72 hours. 16 These criteria indicated that there were 5 out of 7 patients were categorized as severe COVID-19 sufferers in this case series.…”
Section: Discussionmentioning
confidence: 91%